PENGARUH PERSEPSI KEMUDAHAN, KEAMANAN DAN KERAHASIAAN, SERTA KESIAPAN TEKNOLOGI INFORMASI TERHADAP PENGGUNAAN E-FILLING PADA WAJIB PAJAK - Rini Setiawati; Mellya Embun Baining; Mutmainnah (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to examine the effect of perceptions of ease, security and confidentiality, as well as information technology readiness to the use of e-filing for taxpayers. This research data uses primary data by distributing questionnaires to individual taxpayers who are registered at KPP Pratama Pelayangan Jambi City. The sampling method for this research sample is purposive sampling with a sample of 100 taxpayers. The data analysis method used in this research is multiple regression analysis assisted by the IBM SPSS statistics 27 application. The results of this study indicate that perceived ease of use does have a positive effect on the use of e-filing, security and confidentiality do not affect the use of e-filing, while information readiness has a positive effect on the use of e-filing. Simultaneously the independent variables, namely perceived convenience, security and confidentiality, as well as information technology readiness, have an effect on the use of e-filing.